Principles of Money, Banking, and Financial Markets. - Vrooman, David H.; Ritter, Lawrence S.; Silber, William L. (Journal of Finance, 1975)
Part 1 The basics: introducing money money, the economy and inflation financial instruments and markets financial institutions - purposes and profile calculating interest rates the level of interest rates. Part 2 Intermediaries and banks: the regulation and structure of depository institutions commercial bank asset and liability management nondeposit financial institutions international banking financial innovation the payments system. Part 3 The art of central banking: who's in charge here? bank reserves and the money supply the instruments of central banking understanding movements in bank reserves hitting the monetary targets budget deficits and the money supply. Part 4 Monetary theory: the foundations of monetarism the Keynesian framework the ISLM world monetarists and Keynesians in the ISLM world monetarists and Keynesians - an aggregate supply and demand perspective rational expectations - theory and policy implications empirical evidence on the effectiveness of monetary policy. Part 5 Financial markets and interest rates: risk and portfolio choice flow of funds accounting - a framework for financial analysis the structure of interest rates the structure and performance of securities markets the government securities market other fixed-income markets - corporate bonds, municipals, and mortgages equities, the stock market and interest rates financial futures and options. Part 6 International finance: foreign exchange rates fixed versus floating exchange rates balance of payments accounting the gold standard epilogue - careers in banking and financial markets.